Are locally sourced grass or leaf meals a double-edged sword in poultry broiler production? a comprehensive review - Ong, Yee Lyn; Chung, Eric Lim Teik; Nayan, Nazri; Tan, Ngai Paing; Jesse, Faez Firdaus Abdullah; Sazili, Awis Qurni (Malaysian Society of Applied Biology, 2024)
Although antibiotics have considerable positive impacts on poultry production, the use of antibiotics as growth promoters is beginning to diminish as countries continue to prohibit their use, raising concerns about food safety. Consequently, the hunt for antibiotic alternatives is intensified to prevent antimicrobial resistance while not jeopardizing broilers’ growth performance. Phytobiotics are of great relevance since, in addition to being derived from plants, they possess valuable pharmacological properties that may benefit the production performances and health status of broilers. Hence, this review will cover the use of grass or leaf meals as a feed additive in broiler diets, as well as the impact on broiler productivity and meat quality. Locally sourced grass or leaf meals could potentially be used as an antibiotic replacement due to bioactive compounds present, however, these very same compounds are deemed to be detrimental if present in high amounts. Therefore, if the appropriate inclusion level is adopted, the addition of grass or leaf meals might successfully be used as an antibiotic alternative while also improving broiler performance and end-product quality.